Propositional Speech and Stuttering - Hegde MN (Journal of All India Institute of Speech and Hearing, 1970)
One of the attempts that were made to account for the obvious variability in stuttering shown by almost all the stutterers was to relate stuttering to communicative responsibility (Eisenson  1958;  Bloodstein  1950).   Accordingly, the hypothesis put forward by Eisenson (1958) considered stuttering as a 'transient disturbance in communicative, propositional language usage' (p. 244).   This viewpoint holds that meaningful verbal communication or propositional speech is a significant factor that elicits stuttering.   A study by Eisenson and Horowitz (1945) showed that stutterers experience more difficulty in reading a meaningful passage than when they are reading a nonsense selection.   The authors concluded that 'As meanings and the responsibility for communicating meanings become prominent, stuttering increases'.   In other words,  a  proposition, which is a 'unit of meaningful linguistic content' (Eisenson 1958, p. 238) induces stuttering and a nonsense material which is not propositional does not do so.   That is why stutterers do not have considerable difficulty in speaking to children, inferiors, intimate friends and the like.